(3JGQjN KZQ YOfs - (3YHO Gddg Hf YHO Gddg Hf CMeO eNQeI, CHh eMeO , GdWjH HGeNQeI,J (B947 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdSehGJ hGdCQV , hOHQ GdCTjGA HGdEHQGe hGdfbV s
(3BNQgG (B:s
(3hGddg CYde HGdUhGH hEdjg GdeQLY hGdeBH hMSHfG Gddg hfYe Gdhcjd s
(3hgh Ydi bSejfs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B94 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B45s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B239 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B62 s
Keywords: (3GdJGQjNs